CLINICAL STUDY OF OPTIMIZED APPROACHES TO LOCAL PREVENTION OF DENTAL CARIES IN PATIENTS WITH TYPE 1 DIABETES MELLITUS - O.A. Udod; A.S. Kulish (Український стоматологічний альманах, 2019)
The prevalence of dental caries is high in people with type 1 diabetes mellitus and it is about 81.1-100%, however 57.1% are diagnosed with multiple dental caries. The effectiveness of caries prevention is only 48.3%. In the prevention of dental caries has significant role to exogenous methods of prevention with fluorides, but fluoride compounds adversely affect the condition of patients with diabetes mellitus. It’s advisable to use in patients with caries preventive measures containing nanohydroxyapatite and xylitol.